NATIVE CONSTITUTIONAL ANATOMY IN THE ASPECT OF THE PERSONIFICATIVE MEDICINE - V. N. Nikolenko; D. B. Nikityuk; S. V. Chava (Сеченовский вестник)
Modern personificative medicine uses a high technological methods of diagnostics; the treatment is based on using the results of fundamental sciences including constitutional anatomy. A field of its scientific interests is a study of peculiarities of individual and typological changeability of body construction. A lot of new completed papers and dissertations attest about significant practical using of the anatomo-antropometric method. This method can be used in individual clinical and prophylactic medicine due to its simplicity.